2016
DOI: 10.1002/jbm.b.33774
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of wound healing by ultrasound activation of TiO2 in Escherichia coli‐infected wounds in mice

Abstract: Surgical site infections continue to be a common complication affecting surgical prognosis. Reactive oxygen species (ROS) are generated by ultrasound-irradiated titanium dioxide (TiO ) (UIT). Although excessive ROS production can cause cell damage, ROS at physiological levels mediate beneficial cellular responses, including angiogenesis. This study investigated whether UIT can promote healing of Escherichia coli-infected wounds. We used TiO and ultrasound irradiation using an ultrasonography machine at a frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…This in vivo data is comparable with the results of the CAM assay (Figure ). In support to our data, earlier study showed that simultaneous application of ultrasound and TiO 2 nanoparticles promoted neovascularization in mice models . The most plausible reason for the enhanced wound healing could be due to the ability of TiO 2 nanoparticles to generate ROS in biological system .…”
Section: Resultssupporting
confidence: 91%
“…This in vivo data is comparable with the results of the CAM assay (Figure ). In support to our data, earlier study showed that simultaneous application of ultrasound and TiO 2 nanoparticles promoted neovascularization in mice models . The most plausible reason for the enhanced wound healing could be due to the ability of TiO 2 nanoparticles to generate ROS in biological system .…”
Section: Resultssupporting
confidence: 91%
“…It is also been proven that the ROS generation achieved by the external activation of membrane-bound NADPH oxidase can induce angiogenesis and other essential functions of endothelial cells, such as hemostasis (Kim et al, 2017;Aldosari et al, 2018). The activation of angiogenesis caused by an increase in ROS production to restore ROS physiological levels, can be beneficial not only for CVD, as occurs after ischemia (Urao et al, 2008), but can also contribute to wound healing (Osumi et al, 2017). On the other hand, an excessive production of ROS leads to a disequilibrium redox state, where the antioxidant defenses of the cell has been overcome, being responsible for damaging cellular components, as lipids, proteins and DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound therapy could enhance the penetration of NP into the tissues to treat deeper infected sites. Figure 10 shows (a) images of the infected wounds treated with or without using ultrasound-activated TiO 2 NPs, (b) curves illustrating relative wound size percentage calculated compared to the initial wound size [304].…”
Section: Nanotechnology For Treatment Of Burn Infections and Woundmentioning
confidence: 99%